PENERAPAN METODE READING GUIDE MENGGUNAKAN KARYA SASTRA FIKSI UNTUK MENINGKATKAN KEMAMPUAN MEMAHAMI ISI BACAAN SISWA KELAS IV SDN NO. 20 INPRES SOMBA KECAMATAN SENDANA KABUPATEN MAJENE - Astika Yanti; Andi Dewi Riang Tati; Nurhaeda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
One important element in education is reading. This research is motivated by the discovery of several literacy issues at SDN No. 20 Inpres Somba, where almost all students can read but struggle to understand what they have read. Not only that, but students also have difficulty making statements that correspond to the reading text. Furthermore, it was found that some students are unable to determine the theme of a reading, struggle to retell the text in their own words, and have difficulty drawing conclusions from a reading text. This study aims to analyze the implementation of the Reading Guide method using fictional literary works to improve students' reading comprehension skills. The Reading Guide method is a teaching strategy designed to help students organize information and enhance their understanding of the text. In this research, fictional literary works were chosen as a learning medium due to their ability to engage students and provide a rich context for exploring meaning. The research method used is Classroom Action Research. The subjects of the study consisted of 13 fourth-grade students at SDN No. 20 Inpres Somba. The results showed that the implementation of the Reading Guide method in teacher activities during the first cycle resulted in a "sufficient" category and improved to a "good" category in the second cycle. The application of the Reading Guide method in student activities during the first cycle resulted in a "good" category with a percentage that was not yet satisfactory, and improved in the second cycle to a "good" category with a satisfactory percentage. Additionally, the learning outcomes using this method in the first cycle resulted in a "low" category and significantly improved to a "high" category in the second cycle.